Endothelial function evaluation in patients with anorexia nervosa. Issue 3 (2016) - Suntharos, Patcharapong; Jones, Myriam E Almeida; Seiden, Howard S; Fisher, Martin; Gruber, Dorota; Rosen, Lisa M.; Blaufox, Andrew D; Cooper, Rubin S.
No abstract available